Evaluation of the Genetic Diversity of African Yam Bean (Sphenostylis stenocarpa (Hoechst. ex. A Rich.) Harms.) Using Seed Protein Marker - , Josephine Imeh Usoroh; , Effiom E. Eneobong; , Solomon Okon Abraham; , Anthony John Umoyen (Archives of Current Research International, 2019)
Aims: The present research seeks to assess the genetic diversity of African yam bean accessions in Nigeria using seed protein marker; geared towards its genetic improvement and conservation. Introduction: African yam bean is an “Orphan Crop” highly nutritious and has been listed to be among the underutilized legumes despite its immense nutritional advantages in human diets. African yam bean has been reported as a good source of essential amino acids including cysteine, lysine, methionine, phenylalanine and Proline. Study Design: Fifteen (15) accessions of African yam bean were collected from the International Institute for Tropical Agriculture (IITA), Ibadan and 25 local accessions were collected from different parts of Nigeria including Enugu. Results: This study evaluated the genetic diversity on forty (40) accessions of African yam bean (Sphenostylis stenocarpa) obtained from IITA germplasm bank and other parts of Nigeria. In this study, the genetic differences among the accessions were detected by the presence or absence of bands, which could be used as a basis for variation among accessions. The results from this present study revealed high polymorphism (≈93%), indicating high intra-specific genetic variation with potential linkage to traits desired by breeders. Conclusion: The study demonstrated that seed storage protein using SDS-PAGE is an important tool for genetic diversity study in African yam bean, providing baseline information. This baseline information will be useful in further molecular studies geared toward efficient breeding and conservation strategies for this crop.